Goniometry of elbow carrying angle: a comparative clinical study on sexual dimorphism in young males and females - Bari, Wasim; Alam, Masroor; Omar, Saif (International Journal of Research in Medical Sciences, 2017)
Background: Carrying angle of the elbow joint is an angle formed between the axis of arm and axis of forearm in an extended elbow joint supinated at the radio-ulnar joints. It is an obtuse angle which facilitates free swinging of arm by deviating it from the pelvis during walking or carrying an object. Carrying angle increases with age and is reportedly greater in females. Morphometry of this angle may be helpful in identification of elbow disorders along with surgical reconstruction and evaluation of traumatic elbow. The aim of this study was to clinically observe sexual dimorphism of carrying angle among young males and females with normal anatomy and bony configuration of elbows between 21 to 25 years of age the in the outdoor clinic of the Department of Orthopaedics. Methods: Four hundred individuals of equal sex ratio underwent bilateral goniometry. The measurement of carrying angle was performed using goniometer. Results: Carrying angle was observed to be greater in females. There was no correlation between carrying angle and height of individual or length of forearm. Conclusions: Carrying angle is greater in females may be because exhibits high sexual dimorphism. It may also considered be as a secondary sexual characteristic. Utility of goniometry of carrying angle is observed during orthopaedic reconstruction of elbow disorders after treatment of distal fractures of humerus and evaluation of traumatic injuries at the elbow joint.